THE INFLUENCE OF CHATGPT USAGE ON STUDENT LEARNING OUTCOMES IN THE ALGORITHM AND PROGRAMMING COURSE AT UNIVERSITAS AL-KHAIRIYAH - Swastika, Rulin; Rahayu, Didda Yuliana (Jurnal TAM (Technology Acceptance Model), 2025)
This study aims to analyze the influence of ChatGPT usage on student learning outcomes in the Algorithms and Programming course at Universitas Al-Khairiyah. The background of this research is rooted in the growing adoption of artificial intelligence (AI) technologies in education, particularly in supporting the understanding of complex concepts. A quantitative approach was used, with data collected through a linear scale (1–4) questionnaire distributed to students. The analysis results show a strong and significant relationship between the use of ChatGPT and student learning outcomes, with a correlation value of 0.672. Furthermore, the coefficient of determination (R²) of 0.452 indicates that ChatGPT usage contributes 45.2% to the variation in student achievement. These findings demonstrate that effective use of ChatGPT can enhance students' conceptual understanding, task completion efficiency, and overall academic performance. Therefore, ChatGPT can be considered a promising learning tool to improve the quality of education in the field of technology and informatics.